2023
DOI: 10.3171/2023.1.focus22639
|View full text |Cite
|
Sign up to set email alerts
|

Acute low-pressure hydrocephalus in aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE Acute and chronic hydrocephalus are common pathologies after aneurysmal subarachnoid hemorrhage (SAH). Generally, the presence of acute hydrocephalus is associated with elevated intracranial pressure (ICP) treated with a ventricular drain. Subsequently, however, pronounced hydrocephalus without elevated ICP may develop in some patients with SAH in the postacute phase. This is described as acute low-pressure hydrocephalus (aLPH), and there are very limited data in the literature of this pathology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, multiple studies have shown that the amount of blood in the cerebral cistern, ventricle, or brain parenchyma after subarachnoid hemorrhage, as well as acute hydrocephalus, is associated with the formation of chronic hydrocephalus in patients with aSAH ( 19 , 20 ). Although the occurrence of hydrocephalus after aSAH has been well studied and some preventive measures have been taken, its potential risk factors are still unclear ( 21 23 ). Therefore, it is necessary to study the relationship between patients with intraventricular hemorrhage and the formation of chronic hydrocephalus, as well as how to reduce the incidence of chronic hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies have shown that the amount of blood in the cerebral cistern, ventricle, or brain parenchyma after subarachnoid hemorrhage, as well as acute hydrocephalus, is associated with the formation of chronic hydrocephalus in patients with aSAH ( 19 , 20 ). Although the occurrence of hydrocephalus after aSAH has been well studied and some preventive measures have been taken, its potential risk factors are still unclear ( 21 23 ). Therefore, it is necessary to study the relationship between patients with intraventricular hemorrhage and the formation of chronic hydrocephalus, as well as how to reduce the incidence of chronic hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…The modified Rankin Scale (mRS) and Karnofsky Performance Scale (KPS) were used to assess neurologic outcome. An mRS score ≤ 2 was defined as a favorable functional outcome and an mRS score ≥ 3 was defined as a poor functional outcome 10 …”
Section: Methodsmentioning
confidence: 99%
“…An mRS score ≤ 2 was defined as a favorable functional outcome and an mRS score ≥ 3 was defined as a poor functional outcome. 10…”
Section: Neuroradiologic Studies and Assessment Of Prognosis Outcomementioning
confidence: 99%
“…Recent research suggests that the cerebral lymphatic system may be implicated in the etiology of aneurysmal SAH-induced acute low pressure hydrocephalus. 44 Meningeal lymphatic vessels have been recognized as an important player in the complex circulation and exchanges of soluble contents (cytokines) between the CSF and ISF. 45 The brain parenchyma produce a large portion of CSF and drained through the perivascular glymphatic system and meningeal lymphatic vessels into the blood.…”
Section: Other Perspectivesmentioning
confidence: 99%